The utility of gradient of end-tidal carbon dioxide between two lungs in lateral decubitus position in predicting a drop in oxygenation during one-lung ventilation in elective thoracic surgery- A prospective observational study - Swapnil Yeshwant Parab (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Baseline difference in the perfusion of two lungs is the cause of intra-operative shunt during one-lung ventilation (OLV). This study aimed to test the hypothesis that the gradient of end-tidal carbon dioxide (EtCO2) between two lungs in lateral position (D-EtCO2lateral) would predict the quantity of shunt and hence the drop in the oxygenation during OLV. Methods: An observational study was conducted to include consecutive 70 patients undergoing thoracic surgery using a double-lumen tube in a lateral position. D-EtCO2lateral was calculated by subtracting EtCO2 from the non-dependent lung from that of the dependent lung when ventilation parameters are the same for each lung. Oxygenation was assessed by measuring PaO2/FiO2 ratios (P/F ratio) at 10, 20 and 40 min after OLV. Correlations between D-EtCO2lateral and P/F ratios were calculated. Receiver operating curves were analysed to test the ability of D-EtCO2lateral to identify patients with a P/F ratio of <100 during OLV. Results: A moderate correlation was found between D-EtCO2lateral and P/F ratios at 10 and 20 min of OLV. Among lung resection cases (n = 61), correlation was moderate at 10 (r = 0.64), and 20 min (r = 0.65) (P < 0.001) and became weak at 40 min (r = 0.489, P < 0.001). Areas under curve for D-EtCO2lateral to predict the drop in P/F ratio <100 at 10, 20 and 40 min after OLV were 0.90 (cut-off: 2.5), 0.78 (cut-off: 3.5) and 0.78 (cut-off: 4.5), respectively. Conclusion: D-EtCO2lateral could predict the drop in oxygenation in the early part of OLV in lung resection surgeries.